Music computer in teaching the “Listening to Music” course - Gorbunova, Irina B. (2020)
The “Listening to Music” course is an important link in the music education of a child. The “Listening to Music” course fosters love and interest in music, teaches to understand its language, and develops emotional responsiveness in children. The article considers new opportunities in teaching the “Listening to Music” course, which appeared along with a music computer, and which is more often used in the children's music school and meets the requirements of modern pedagogy. The article describes the capabilities of music and computer programs aimed at developing creative abilities of children. The authors examined new forms of work in the classroom using a music computer. The article proves that using a musical computer opens up broad prospects for employing creative tasks at children's music and art schools.